Character and laxative activity of polysaccharides isolated from Dendrobium officinale. (July 2017) - Luo, Dandan; Qu, Cao; Lin, Guosheng; Zhang, Zhenbiao; Xie, Jianhui; Chen, Hanbin; Liang, Jiali; Li, Cailan; Wang, Hongfeng; Su, Ziren
Highlights: D. officinale polysaccharides (DOP) were mainly composed ofd -mannose andd -glucose. DOP were the laxative ingredients of D. officinale . DOP promoted gastrointestinal transit ratio and faecal water content. DOP normalized the levels of gut hormones such as gastrin, motilin and somatostatin. DOP represent a promising dietary therapy for constipation. Abstract: Dendrobium officinale was separated into total polysaccharides (DOP) and supernatant (DOS) to investigate the laxative ingredients and mechanism in normal and constipated mice induced by diphenoxylate or water fasting. The molecular weight and components of DOP were determined by HPGPC, HPLC and LC-MS. DOP was mainly composed ofd -mannose (59.19 mg/g) andd -glucose (830.98 mg/g), with a molecular weight of 8404 Da. DOP (29, 57, 114 mg/kg, i.g.) exhibited an appreciable laxative effect in normal mice ( p  < 0.05), while DOS (35, 70, 140 mg/kg, i.g.) did not. DOP significantly enhanced the GI transit ratio; recovered the faecal output characteristics; obviously increased the levels of Gas, MTL, AChE and SP; and decreased the levels of SS in constipated mice (all p  < 0.05). The current study suggested that DOP is the laxative component of D. officinale and can be used as a promising dietary therapy for constipation in daily life.